The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1442-200x.2009.02965.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in epileptic children

Abstract: Epileptic children are at an increased risk of developing caries and gingivitis compared with healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…The dental conditions of epilepsy patients were significantly worse than non-epileptic age-matched groups. furthermore, poorly controlled epilepsy patients had worse oral health compared to patients who had better controlled epilepsy (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental conditions of epilepsy patients were significantly worse than non-epileptic age-matched groups. furthermore, poorly controlled epilepsy patients had worse oral health compared to patients who had better controlled epilepsy (29).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs alter the metabolism and cause osteopenia and osteomalacia by leading clearance of vitamin D (29). Anticonvulsant drugs cause changes in bone metabolism and calcium levels and these drugs may lead to a decrease in bone mass (39).…”
Section: Discussionmentioning
confidence: 99%
“…The subjects that took antiepileptic medicines had significantly higher OHI-S index (2.50), unlike the subjects not taking medicine (1.53), (p=0.0001; Z=4.92). In the study by Gurbuz, who looked at epileptic patients, achieved a lower DMFt number value (3.5±3.79) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Gurbuz et al (Gurbuz & Tan, 2010) found a traumatic anterior dental injury rate of 68.8% in children with epilepsy in Erzurum, Turkey. This probably resulted from insufficient seizure control or from placing hard objects between the teeth of patients during seizures.…”
Section: Dental Status and Oral Health 421 Traumamentioning
confidence: 99%